Fotografia e profilaxia social : a visão do «outro» nas campanhas da LPPS - Heras Herrero, Beatriz de las (2015)
The Portuguese League for Social Prophylaxis is, since 1924, an institution dedicated to defending public health. It developed an action programme targeted at raising the awareness of the population to the risks of contagious diseases and some social practices, questioning the physical, psychological and moral dimensions. In its direct action with «others», the League used media such as photographs and posters, as well as the cinema. This article intends to explore the League's visual production, aiming to analyse the message issued regarding health education in the period between the two world wars, focusing on the posters produced for this purpose, as well as the foreign posters that served as inspiration.